Dampak Pandemi Covid-19 Pada Nilai Indeks Harga Saham Gabungan (IHSG) Di PT. Bursa Efek Indonesia ( BEI ) - Novalita, Novalita; Bakti, Umar (Akuisisi : Jurnal Akuntansi, 2022)
This study was conducted to determine the impact of the COVID-19 pandemic virus in Indonesia on inflation, interest rates, as well as the composite stock price index in PT. Indonesia Stock Exchange. The COVID-19 pandemic virus is an infectious disease caused by SARS-CoV-2. The COVID-19 Pandemic virus has a huge impact on Indonesia, including in the economic, socio-cultural, and rupiah exchange rates. The results of this study can be concluded that the COVID-19 pandemic virus in Indonesia has lowered the Indonesian economy due to the decline in the Jakarta Composite Index. Indonesian Stock Exchange and rising interest rates and inflation rates in Indonesia.